Physical Fitness Analysis of Student Learning Outcomes - Wenda Wulan Agustin; Hartati Hartati; Silvi Aryanti (Universitas Negeri Medan, 2021)
The aims of this study was to find out about physical fitness, learning outcomes, and the relationship of physical fitness for learning outcomes of thhird semester Physical education and Health student FKIP Sriwijaya University.The type research used in descriptive and with a correlation design. The population of this research is the third semester students. The sample ini this study was 67 students of the third semester. The instruments used harvard stept tes and secondary data from learning outcomes on the cumulative grade point index (IPK). Technique for analysis data was processed by percentage and used computer assistance trough the SPSS 22 program. Based on the analysis of persentage of data obtained, the result of student physical fitness obtained a persentage of 81% amounting to 54 student with very good categories, 15% amounting to 10 student ini good categories, and 4% amounting to student with enough categories. Learning outcomes (IPK) of students obtaines a percentage 0f 73% amounting to 49 student with praise, and 27% of 18 student with satisfying predicates. The result of the correlation test data analysis technique r=0,000 less than 0,05, indicate that there is a significant relationship between physical fitness and student learning outcomes. The result of the interpretation of the coefficient is=0,598 which includes a moderate level of relationship and cotributes 34,8%. The implication of this research is that good physical fitness will be able to affect the achievement of good learnig outcomes. Kata Kunci: Hasil Belajar, Kebugaran Jasmani, Mahasiswa